Method for producing polyolefin composition and method for producing molded product containing polyolefin composition

By surface modification of natural fibers and mixing them with vinyl polymers containing epoxy groups to form a polyolefin composition with high rigidity and high impact strength, the problem of unbalanced rigidity and impact strength of the material in the prior art is solved, and the efficient compatibility and environmental protection of the material are achieved.

JP2025014840APending Publication Date: 2025-01-30SEIKO PMC CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023117737
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

In the prior art, when natural fibers and glass fibers are used as resin reinforced materials, it is difficult to achieve a balance between high rigidity and high impact strength at the same time, and there are problems with material recycling and environmental protection treatment.

Method used

By modifying the natural fiber surface to a vinyl polymer containing a carboxyl group and mixing it with a vinyl polymer containing an epoxy group, a polyolefin composition with high rigidity and high impact strength is formed.

Benefits of technology

The balance between high rigidity and high impact strength of polyolefin materials is achieved, the compatibility and recycling of materials are improved, and the problems of material weight and environmentally friendly treatment are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014840000001
    Figure 2025014840000001
  • Figure 2025014840000002
    Figure 2025014840000002
  • Figure 2025014840000003
    Figure 2025014840000003
Patent Text Reader

Abstract

To provide a method for producing a polyolefin composition with superior rigidity and impact properties, and a method for producing a molded product containing the polyolefin composition.SOLUTION: A method for producing a polyolefin composition includes the following steps: (1) mixing cellulose fibers (a1) with a vinyl polymer (a2) having carboxyl groups to prepare a cellulose fiber mixture (A1); and (2) mixing the cellulose fiber mixture (A1), polyolefin (B) and an olefin polymer (C) having epoxy groups.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polyolefin composition having excellent rigidity and impact properties, and a method for producing a molded article containing the polyolefin composition. [Background technology]

[0002] Traditionally, talc and glass fiber have been used as reinforcing materials for resins used in molding materials. Talc is inexpensive, but the required mechanical properties cannot be obtained unless a large amount is added, resulting in a heavy molded product. Glass fiber is also relatively inexpensive, but material recycling is difficult because the fibers are cut during molding processing, and materials containing glass fiber are difficult to incinerate, so they must be disposed of in landfills, making them less recyclable.

[0003] On the other hand, cellulose fibers are derived from natural products and have excellent recyclability. They are also lighter than other reinforcing materials, and the cellulose fibers themselves have a high elastic modulus. As a result, there are high expectations for them to be used as a reinforcing material for resins, and technological development is currently underway.

[0004] For example, Patent Document 1 discloses a resin composition having bending strength, tensile strength and bending modulus suitable for use in applications such as molded parts for automobile interiors and molded parts for the exteriors of home appliances, which is obtained by blending an epoxy-containing polypropylene (hereinafter sometimes abbreviated as PP) with a resin composition consisting of cellulose fibers and a polyolefin resin. Furthermore, Patent Document 2 discloses a resin composition having a high elastic modulus, in which the hydrophilic cellulose fiber surface is modified with a water-insoluble styrene / acrylic resin to improve the dispersibility of the cellulose fiber in a hydrophobic polyolefin resin.

[0005] However, neither Patent Document 1 nor Patent Document 2 mentions the impact strength required for structural materials. In Patent Document 1, hydrophilic plant fibers are blended directly into hydrophobic resin, so the plant fibers aggregate in the resin and a sufficient reinforcing effect cannot be achieved, and in Patent Document 2, when a styrene / acrylic resin is blended to modify the surface of cellulose fibers, the elastic modulus is improved but the desired impact strength is not achieved. The physical properties required for structural material molded parts are rigidity, i.e., high elastic modulus, and high impact strength.

[0006] [Patent Document 1] International Publication No. 2013 / 099530 [Patent Document 2] International Publication No. 2020 / 235310 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a method for producing a polyolefin composition having excellent rigidity and impact properties, and a method for producing a molded article containing the polyolefin composition. [Means for solving the problem]

[0008] Means for Solving the Problems The inventors conducted extensive research in light of the above problems and discovered that by further blending an olefin polymer containing an epoxy group with cellulose fibers whose surface has been modified with a vinyl polymer having a carboxyl group, it is possible to obtain a polyolefin composition which not only improves the elastic modulus but also exhibits high impact strength, thereby completing the present invention.

[0009] That is, the present invention provides: <1> A step (1) of mixing cellulose fibers (a1) with a vinyl polymer (a2) having a carboxyl group to obtain a cellulose fiber mixture (A1); A step (2) of mixing the cellulose fiber mixture (A1), a polyolefin (B) and an olefin polymer containing an epoxy group (C). A method for producing a polyolefin composition comprising the steps of: <2> The vinyl polymer (a2) having a carboxyl group comprises at least one selected from the group consisting of styrene / (meth)acrylic resin and (meth)acrylic resin. <1> A method for producing the polyolefin composition according to claim 1, <3> The epoxy group-containing olefin polymer (C) is a reaction product (C1) of a (meth)acrylate having a glycidyl group with polypropylene and / or a copolymer (C2) of a (meth)acrylate having a glycidyl group with propylene, and is characterized in that the following (i) and (ii) are satisfied: <1> A method for producing the polyolefin composition according to claim 1, (i) The cellulose fiber (a1) contains 5 parts by mass or more and 1,000 parts by mass or less of an olefin polymer (C) containing an epoxy group relative to 100 parts by mass of the cellulose fiber (a1). (ii) The epoxy equivalent of the epoxy group-containing olefin polymer (C) is 142 or more and 23,000 or less. <4> The epoxy group-containing olefin polymer (C) is a reaction product (C3) of a (meth)acrylate having a glycidyl group, a styrene, and polypropylene, and / or a copolymer (C4) of a (meth)acrylate having a glycidyl group, a styrene, and propylene. <1> A method for producing the polyolefin composition according to claim 1, <5> The above <1> ~ <4> A method for producing a molded article, comprising using a polyolefin composition obtained by the method for producing a molded article according to any one of claims 1 to 5. It is. Effect of the Invention

[0010] According to the present invention, it is possible to provide a polyolefin composition having excellent rigidity and impact properties, and also to provide a molded article made of the polyolefin composition that can be used for various applications.

[0011] The cellulose fiber mixture (A1) of the present invention can efficiently and uniformly disperse the inherently highly hydrophilic cellulose fibers in the polyolefin resin without agglomeration by premixing the cellulose fibers (a1) with the vinyl polymer (a2) having a carboxyl group to hydrophobically modify the cellulose fiber surface. In addition, the olefin polymer (C) containing an epoxy group has both a polar epoxy group and a non-polar polyolefin structure, so that the compatibility of the cellulose fiber mixture (A1) with polyolefins can be further improved. As a result, the rigidity of the polyolefin composition can be further increased. Furthermore, the carboxyl groups (including the hydrolyzate of a carboxylic anhydride) on the surface of the cellulose fiber mixture (A1) can react partially / all with the epoxy groups of the olefin polymer (C) containing an epoxy group to form a crosslinked structure. In addition to the network of cellulose fibers, the presence of a gentle crosslinked structure between the cellulose fibers and the olefin polymer (C) containing an epoxy group is believed to absorb external stress and improve not only the rigidity but also the impact properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the method for producing a polyolefin composition of the present invention, (1) a step of mixing cellulose fiber (a1) with a vinyl polymer (a2) having a carboxyl group to obtain a cellulose fiber mixture (A1) is followed by (2) a step of mixing the cellulose fiber mixture (A1) with a polyolefin (B) and an olefin polymer (C) containing an epoxy group. Hereinafter, an embodiment of the present invention will be described in detail. Note that the following description is an example of an embodiment of the present invention, and the present invention is not limited to this description.

[0013] <Step of obtaining cellulose fiber mixture (A1)> In the present invention, the cellulose fiber mixture (A1) is obtained by mixing the cellulose fiber (a1) with the vinyl polymer (a2) having a carboxyl group. The mixing method is not particularly limited as long as the cellulose fiber (a1) can be mixed with the vinyl polymer (a2) having a carboxyl group. For example, there are a method of directly mixing the cellulose fiber (a1) with the vinyl polymer having a carboxyl group, a method of mixing the vinyl polymer having a carboxyl group at a temperature above the melting point if the vinyl polymer having a carboxyl group (a2) is solid at room temperature, and a method of mixing the vinyl polymer having a carboxyl group (a2) with water and / or an appropriate organic solvent such as alcohol or glycol ether, and then mixing it with the cellulose fiber (a1), and then removing the water and / or the organic solvent.

[0014] The cellulose fibers (a1) are known to be derived from plants (e.g., wood, bamboo, hemp, cotton, jute, kenaf, agricultural waste, cloth, pulp (unbleached softwood kraft pulp, bleached softwood kraft pulp, unbleached hardwood kraft pulp, bleached hardwood kraft pulp, unbleached softwood sulfite pulp, bleached softwood sulfite pulp, thermomechanical pulp, recycled pulp, waste paper, etc.)), animals (e.g., ascidians), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), microbial products, etc., and any of these can be used in the present invention. Cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred. Among cellulose fibers derived from plants, pulp (particularly unbleached softwood kraft pulp and bleached softwood kraft pulp) is particularly preferred.

[0015] The cellulose fibers (a1) may be either microfibrillated or nanofibrillated by defibration treatment in advance using a bead mill, high-pressure homogenizer, jet mill, ultrasonic agitator, stone grinder, etc., or may be undefibrated. When the cellulose fibers (a1) are defibrated in advance, the defibrated state can be confirmed as follows. (1) Cellulose fibers before and after defibration are added to water to a concentration of 0.02 to 0.1%, and then thoroughly dispersed by ultrasonic treatment to prepare each dispersion. (2) Next, one drop of each dispersion is placed on a glass petri dish, covered with a cover glass to remove excess liquid, and then observed at 100 to 500 times magnification using an optical microscope to measure the fiber length and fiber diameter of the cellulose fibers before and after defibration. If the fibers have become thinner due to the defibration process, they cannot be seen using a polarizing microscope, so the fiber diameter of the defibrated fibers is measured by observation using an electron microscope. (3) Confirm that there is a difference in fiber length and diameter before and after defibration.

[0016] The vinyl polymer (a2) having a carboxyl group functions as a hydrophobizing agent for hydrophobizing the surface of the cellulose fiber (a1), and must contain at least both a carboxyl group having good affinity with cellulose and a hydrophobic group for hydrophobizing the cellulose surface in the molecule. Specifically, it is a vinyl polymer that is a polymer of a monomer mixture containing a vinyl monomer having a carboxyl group and a vinyl monomer having hydrophobicity. The vinyl polymer having a carboxyl group preferably has an acid value of 10 to 200 mgKOH / g, a weight average molecular weight of 5,000 to 200,000, and a glass transition temperature of 40 to 150°C. In the present invention, the vinyl polymer having a carboxyl group is more preferably a styrene / (meth)acrylic resin or a (meth)acrylic resin. Examples of the styrene / (meth)acrylic resin include styrene / acrylic acid resins, which are typified by a polymer of a styrene-based monomer and (meth)acrylic acid, and styrene / (meth)acrylic acid / (meth)acrylic acid ester resins, which are typified by a polymer of a styrene-based monomer, (meth)acrylic acid, and (meth)acrylic acid ester. Examples of the (meth)acrylic resin include (meth)acrylic acid / (meth)acrylic acid ester resins, which are typified by a polymer of (meth)acrylic acid and (meth)acrylic acid ester. Among these, styrene / (meth)acrylic acid resins and styrene / (meth)acrylic acid / (meth)acrylic acid ester resins are particularly preferred. These vinyl-based polymers (a2) having a carboxyl group can be used alone or in combination of two or more.

[0017] Examples of vinyl monomers having a carboxyl group include (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, aconitic acid, and cinnamic acid. These monomers can be used alone or in combination of two or more. Among these, (meth)acrylic acid is preferred. A part or all of the carboxyl group may be in the form of a salt of an alkali metal, an alkaline earth metal, a primary amine, a secondary amine, a tertiary amine, or a quaternary ammonium ion, as long as the effect of the present invention is not impaired. Furthermore, a vinyl monomer having a carboxylic acid anhydride may be used in combination as long as the effect of the present invention is not impaired. Examples of vinyl monomers having a carboxylic acid anhydride include itaconic anhydride, maleic anhydride, fumaric anhydride, citraconic anhydride, and cyclohexene dicarboxylic anhydride.

[0018] The hydrophobic vinyl monomer refers to a vinyl monomer that can be copolymerized with a vinyl monomer having a carboxyl group and dissolves in an amount of 10 g or less in 100 g of water at 25° C. under atmospheric pressure. Examples of the vinyl monomer include (meth)acrylic acid esters and styrene monomers that satisfy the above-mentioned dissolution amount. Specific examples of the (meth)acrylic acid ester include (meth)acrylic acid esters having a linear structure and containing a saturated alkyl group, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, and stearyl (meth)acrylate; (meth)acrylic acid esters having a branched structure and containing a saturated alkyl group, such as isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; (meth)acrylic acid esters having an alicyclic alkyl group, such as cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; and (meth)acrylic acid esters containing aromatic groups, such as phenyl (meth)acrylate and benzyl (meth)acrylate. Specific examples of the styrene monomer include styrene and its derivatives such as styrene, α-methylstyrene, divinylbenzene, 4-methylstyrene, 4-t-butylstyrene, 4-n-octylstyrene, 4-vinylbenzoic acid, 4-aminostyrene, 4-methoxystyrene, 4-nitrostyrene, stilbene, and 4,4'-dimethyl-stilbene. Among these, methyl (meth)acrylate, butyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, styrene, and α-methylstyrene are preferred, and methyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, styrene, and α-methylstyrene are more preferred. These vinyl monomers can be used alone or in combination of two or more kinds.

[0019] In addition, the cellulose fiber mixture (A1) may be used in combination with 10 parts by mass or less of modified cellulose fiber (A2) in which functional groups of cellulose are substituted and modified, based on 100 parts by mass of the cellulose fiber mixture (A1), within a range that does not impair the effects of the present invention. For example, modified cellulose fiber in which the hydroxyl groups of cellulose are esterified with acid anhydrides such as acetic anhydride, propionic anhydride, butyric anhydride, valeric anhydride, hexanoic anhydride, decanoic anhydride, benzoic anhydride, and stearic anhydride, or polybasic acid anhydrides such as maleic anhydride, succinic anhydride, phthalic anhydride, alkyl or alkenyl succinic anhydride, maleic anhydride-modified polyolefin, and maleic anhydride-modified polybutadiene may be used. The modified cellulose fiber (A2) may be used alone or in combination of two or more kinds.

[0020] <Step of Obtaining Polyolefin Composition> In the present invention, the polyolefin composition is obtained by mixing the cellulose fiber mixture (A1) with the polyolefin (B) and the olefin polymer (C) containing an epoxy group. In order to mix more uniformly, it is preferable to mix by melt kneading or semi-melt kneading, and a plurality of mixing steps may be combined. Whether or not the composition is mixed uniformly can be confirmed by the dispersion state of the cellulose fiber (a1) in the polyolefin composition. 0.1 g of the polyolefin composition is taken, and a press film is made by applying a pressure of 10 MPa at 190°C using a heat press machine (manufactured by Toyo Seiki Co., Ltd.), and the number of coarse particles of 1 mm or more is visually counted and judged. The number of particles is less than 5, which is a practical level. The cellulose fiber (a1) may be thinned in this mixing step, that is, defibrated.

[0021] <Kneading equipment> As a mixing device, various methods used for mixing and kneading polyolefins can be used, for example, melt kneading and semi-melt kneading in which the mixture is heated while being mechanically ground using a single-axis or multi-axis kneader, a kneading tester, a pressure kneader, a Banbury mixer, a ball mill, or other mills can be used.

[0022] When a multi-screw kneader is used, a twin-screw kneader is preferred because of its versatility and availability. Either a unidirectional or counter-rotating twin-screw kneader can be used as the twin-screw kneader. The screw length / screw diameter of the twin-screw kneader used in the present invention is usually 15 to 60, preferably 30 to 60. The screw may have a dam structure at one or more locations.

[0023] The kneading temperature is not particularly limited as long as the polyolefin (B) can be melted. When the cellulose fiber (a1) is defibrated by a twin-screw or multi-screw kneader during kneading, the number of treatments (number of passes) varies depending on the fiber diameter and fiber length of the target plant fiber, the physical properties of the desired polyolefin composition, etc., but is usually 1 to 8 times, preferably 1 to 4 times, and more preferably 1 to 2 times. The kneading time is usually 60 minutes or less, preferably 30 minutes or less, and more preferably 15 minutes or less. If the number of passes or kneading time is too long, not only does it reduce productivity, but the plant fiber itself may be thermally deteriorated, leading to deterioration in the color of the polyolefin composition.

[0024] The polyolefin (B) is not particularly limited as long as it is one that is normally used for molding material applications. Specific examples include olefin homopolymers such as polyethylene, polypropylene, and polybutene, ethylene-α-olefin copolymers such as ethylene-propylene copolymers, ethylene-butene copolymers, and ethylene-octene copolymers, ethylene-vinyl acetate copolymers, and ionomer resins. The polyolefin (B) does not contain reactive groups such as carboxyl groups and epoxy groups. As long as the effects of the present invention are not hindered, other thermoplastic resins can also be used in combination. Examples of the thermoplastic resins include polyamide resins such as nylon; polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polylactic acid; acrylic resins such as polymethyl methacrylate and polyethyl methacrylate; styrene resins such as polystyrene and (meth)acrylic acid ester-styrene resins; thermoplastic resins such as cellulose resins, and thermoplastic elastomers such as olefin elastomers, vinyl chloride elastomers, styrene elastomers, urethane elastomers, polyester elastomers, and polyamide elastomers, and mixtures of two or more of these. Among these, it is particularly preferable to use polylactic acid in combination.

[0025] The epoxy group-containing olefin polymer (C) is not particularly limited as long as it has an epoxy group in the main chain and / or side chain of the olefin polymer. For example, it may be obtained by copolymerizing an epoxy group-containing monomer with an olefin, reacting an epoxy group-containing polymer with an olefin polymer, or introducing radicals into polyolefin (B) using peroxide or electron beams and then reacting with an epoxy group-containing monomer. The epoxy groups in the epoxy group-containing olefin polymer (C) may be distributed in any manner on a single polymer chain. For example, the epoxy groups may be introduced randomly, in blocks, in a gradient manner, or only at the terminals. Examples of the epoxy group-containing monomer include allyl glycidyl ether, glycidyl (meth)acrylate, (3,4-epoxycyclohexyl)methyl acrylate, and 4-hydroxybutyl acrylate glycidyl ether. Examples of the olefin include olefin homopolymers such as polyethylene and polypropylene, ethylene-α-olefin copolymers such as ethylene-propylene copolymers, ethylene-butene copolymers, and ethylene-octene copolymers, propylene-α-olefin copolymers, ethylene-vinyl acetate copolymers, etc. Also, acid-modified polypropylenes (d) such as terminally maleic anhydride-modified polypropylenes can be used as the olefin polymers.

[0026] Among the above, the epoxy group-containing olefin polymer (C) is preferably a reaction product (C1) of a (meth)acrylate having a glycidyl group with polypropylene and / or a copolymer (C2) of a (meth)acrylate having a glycidyl group with propylene and / or a reaction product (C3) of a (meth)acrylate having a glycidyl group, a styrene and polypropylene and / or a copolymer (C4) of a (meth)acrylate having a glycidyl group, a styrene and propylene in terms of the mechanical properties of the polyolefin composition obtained by the present invention.

[0027] Examples of (meth)acrylates having a glycidyl group include glycidyl (meth)acrylate, (3,4-epoxycyclohexyl)methyl acrylate, and 4-hydroxybutyl acrylate glycidyl ether.

[0028] Examples of styrenes include styrene, α-methylstyrene, divinylbenzene, 4-methylstyrene, 4-t-butylstyrene, 4-n-octylstyrene, sodium styrenesulfonate, 4-vinylbenzoic acid, 4-aminostyrene, 4-methoxystyrene, 4-nitrostyrene, stilbene, and 4,4'-dimethylstilbene. Of these, styrene and α-methylstyrene are particularly preferred.

[0029] In the present invention, the amount of the epoxy group-containing olefin polymer (C) used is preferably 5 parts by mass or more and 1,000 parts by mass or less per 100 parts by mass of the cellulose fibers (a1) from the viewpoint of the mechanical properties of the resulting polyolefin composition.

[0030] Moreover, the epoxy equivalent of the epoxy group-containing olefin polymer (C) is preferably 142 or more and 23,000 or less from the viewpoint of the mechanical properties of the resulting polyolefin composition. Here, the epoxy equivalent is defined in JIS K7236 as the mass of a resin containing one equivalent of an epoxy group, and the smaller the value, the greater the epoxy group content. In the present invention, the epoxy equivalent of the olefin polymer (C) containing an epoxy group can be calculated based on the maximum absorbance of the carbonyl peak in FT-IR measurement and a calibration curve prepared in advance by the method described below. Specifically, a calibration curve relating the maximum absorbance of the carbonyl peak in the FT-IR absorbance spectrum of the olefin polymer (C) containing an epoxy group to the content of the monomer containing an epoxy group determined by NMR measurement is prepared in advance, and the content of the monomer containing an epoxy group can be calculated from the FT-IR maximum absorbance of the target olefin polymer (C) containing an epoxy group using the calibration curve, and converted into the epoxy equivalent.

[0031] FT-IR measurements can be performed according to the following procedure. (Preparation of measurement samples) A vessel is charged with 1 part of epoxy group-containing olefin polymer (C) and 5 parts of xylene, which are then heated to 170°C and stirred. After no solid matter is visible, the mixture is reprecipitated with 40 parts of acetone to remove unreacted epoxy group-containing monomers and their homopolymers. The filtered material is dried at 80°C. By purifying the epoxy group-containing olefin polymer (C) through this series of operations, the epoxy groups and functional groups introduced along with the epoxy groups detected in subsequent analyses can be identified as those bound to the olefin polymer. (FT-IR measurement) The absorbance spectrum of the epoxy group-containing olefin polymer (C) is measured using a Fourier transform infrared spectrometer ("Frontier" manufactured by PerkinElmer Japan LLC). For example, in the case of a reaction product (C1) of a (meth)acrylate having a glycidyl group and polypropylene, measurement is performed by single reflection ATR method, and the absorbance spectrum is obtained at 2,910 to 2,960 cm -1 The maximum absorbance of 1,700-1,750 cm -1 The region was assigned as the carbonyl peak, and its maximum absorbance was determined. The presence of a carbonyl peak in the (meth)acrylate structure confirmed that (meth)acrylates having a glycidyl group were bonded to polypropylene.

[0032] When producing the polyolefin composition in the present invention, it is preferable to mix the cellulose fiber composition (A1) / polyolefin (B) / epoxy group-containing olefin polymer (C) in a mass ratio of 2-80 / 5-97.8 / 0.2-15 in order to achieve both rigidity and impact resistance.

[0033] The polyolefin composition obtained by the present invention may contain various additives such as dispersants, surfactants, antioxidants, flame retardants, pigments, dyes, inorganic fillers, plasticizers, UV absorbers, light stabilizers, crystal nucleating agents, and foaming assistants as other components, within the scope of not impairing the effects of the present invention.

[0034] The polyolefin composition obtained by the present invention can be molded by various molding methods such as injection, extrusion, pressing, blowing, and 3D printing. Examples of uses of the molded bodies include interior and exterior materials and housings for transport machinery such as automobiles, motorcycles, bicycles, railways, drones, rockets, aircraft, and ships, energy machinery such as wind power generators and hydroelectric generators, home appliance housings such as air conditioners, refrigerators, vacuum cleaners, microwave ovens, AV equipment, digital cameras, and personal computers, electronic circuit boards, communication device housings such as mobile phones and smartphones, medical instruments such as crutches and wheelchairs, shoes such as sneakers and business shoes, tires, balls for ball games, ski boots, snowboards, golf clubs, protectors, fishing lines, and sports equipment such as artificial bait, outdoor equipment such as tents and hammocks, civil engineering and construction materials such as electric wire covering materials, water pipes, and gas pipes, building materials such as pillar materials, flooring materials, decorative panels, window frames, and insulation materials, furniture such as bookshelves, desks, and chairs, industrial robots, household robots, hot melt adhesives, filaments and support agents for laminated 3D printers, packaging materials such as films and tapes, resin containers such as PET bottles, eyeglass frames, trash cans, and household goods such as mechanical pencil cases. EXAMPLES

[0035] Examples of the present invention will be described below. Note that the present invention is not limited to these examples. Note that, unless otherwise specified, "parts" refers to "parts by mass."

[0036] <Production of vinyl polymer (a2) having carboxyl group> (Synthesis Example 1) 500 parts by mass of propylene glycol monomethyl ether acetate was charged into a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, and the internal temperature was raised to 140° C. while stirring. 100 parts by mass of acrylic acid as a vinyl monomer having a carboxyl group, 150 parts by mass of 2-ethylhexyl acrylate as a vinyl monomer having hydrophobicity, 250 parts by mass of styrene, and 10 parts by mass of di-t-butyl peroxide as a polymerization initiator were charged over 3 hours. After the charging was completed, the internal temperature was kept at 145° C. for 2 hours, and then the unreacted matter and the solvent in the system were removed to obtain a vinyl polymer (a2-1) having a carboxyl group.

[0037] (Synthesis Example 2) A 1-liter four-neck flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube was charged with 20 parts of acrylic acid as a vinyl monomer having a carboxyl group, 80 parts of styrene as a vinyl monomer having hydrophobicity, 2.0 parts of azobisisobutyronitrile and 100 parts of isopropyl alcohol, and the mixture was kept at 80 ° C. for 7 hours, and then 1.0 part of azobisisobutyronitrile was charged and further kept at the same temperature for 3 hours. Next, 51.9 parts of a 30% by mass potassium hydroxide aqueous solution was added, and then 300 parts of water was added, and the temperature was further increased to distill off isopropyl alcohol, thereby obtaining an aqueous dispersion of a vinyl polymer (a2-2) having a carboxyl group.

[0038] <Production of olefin polymer (C) containing epoxy groups> (Synthesis Example 3) 87 parts of polyethylene was charged and melted in a vessel heated to 180°C and stirred at 50 revolutions per minute. 12.5 parts of glycidyl methacrylate dissolved in 0.5 parts of bis(1-t-butylperoxy-1-methylethyl)benzene was added once per minute over a period of 10 minutes. Stirring was continued for another 5 minutes, and the contents were then removed to obtain an olefin polymer (C-1) containing an epoxy group.

[0039] (Synthesis Examples 4 to 7, 14) Except for changing the types and amounts of raw materials as shown in Table 1, epoxy group-containing olefin polymers (C-2, C-6, C-7, C-8, and C-13) were obtained in accordance with the method described in Synthesis Example 3.

[0040] [Table 1] In Table 1, (*1) represents bis(1-t-butylperoxy-1-methylethyl)benzene.

[0041] (Synthesis Example 8) In a reaction vessel equipped with a stirrer, a thermometer, and a reflux condenser, 100 parts of terminally unsaturated polypropylene (Viscol 330P: weight average molecular weight 40,000: manufactured by Sanyo Chemical Industries, Ltd.) and 2.5 parts of maleic anhydride were charged and mixed with stirring. The mixture was heated to 215°C and then stirred for 8 hours. The mixture was taken out in a molten state, cooled, pulverized, and washed with acetone. The mixture was dried at 80°C for 2 hours to obtain a terminally maleic anhydride-modified polypropylene (d-1).

[0042] (Synthesis Example 9) Except for changing the types and amounts of raw materials as shown in Table 2, a maleic anhydride-terminated polypropylene (d-2) was obtained in accordance with the method described in Synthesis Example 8.

[0043] [Table 2] Viscol 660P: Terminally unsaturated polypropylene (weight average molecular weight 10,000: manufactured by Sanyo Chemical Industries, Ltd.)

[0044] (Synthesis Example 10) In a vessel heated to 170°C and stirred at 50 revolutions per minute, 1 part of maleic anhydride-terminated polypropylene (d-1) and 8 parts of ethylene-glycidyl methacrylate copolymer (Bondfast (registered trademark) BF-30C, manufactured by Sumitomo Chemical Co., Ltd.) were charged and melted. After continuing stirring for 15 minutes, the contents were taken out to obtain an epoxy group-containing olefin polymer (C-9) in which epoxy groups were introduced in blocks.

[0045] (Synthesis Examples 11 to 13) Except for changing the types and amounts of raw materials as shown in Table 3, the same procedure as in Synthesis Example 10 was followed to obtain olefin polymers containing epoxy groups (C-10, C-11, and C-12).

[0046] [Table 3]

[0047] <Evaluation of olefin polymer (C) containing epoxy groups> (purification method) The epoxy group-containing olefin polymers (C) synthesized in Synthesis Examples 5 to 7 and 14 were purified according to the method shown below and then 1 Used for HNMR and FT-IR measurements. 1 part of epoxy group-containing olefin polymer (C) and 5 parts of xylene were charged into a vessel, heated to 170°C, and stirred. After no solid matter was observed, the mixture was precipitated with 40 parts of acetone, filtered, and dried at 80°C.

[0048] ( 1 HNMR measurement) An olefin polymer (C) containing an epoxy group is dissolved in a heavy solvent; 1 The resulting spectrum was subjected to HNMR measurement. From the integral ratio of the peak derived from the epoxy group or a functional group having a substance amount equal to a constant multiple of the epoxy group and the peak derived from the olefin polymer, the introduction rate of the epoxy group was calculated, and the content of glycidyl methacrylate was calculated and converted into the epoxy equivalent. For example, in C-6, the epoxy equivalent was calculated from the peak derived from the glycidyl group appearing at 4.3 to 4.7 ppm and the peak derived from the hydrocarbon appearing at 0.5 to 2.4 ppm.

[0049] (FT-IR measurement) The absorbance spectrum of the epoxy group-containing olefin polymer (C) was measured using a Fourier transform infrared spectrometer ("Frontier" manufactured by PerkinElmer Japan LLC). The measurement was carried out by the single reflection ATR method, and the absorbance spectrum was measured at 2,910 to 2,960 cm -1 The maximum absorbance of 1,700-1,750 cm -1 The region was assigned as the carbonyl peak, and its maximum absorbance was determined.

[0050] (Epoxy group introduction rate calculation) The introduction rate of epoxy groups was measured by calculating the epoxy equivalent. The epoxy equivalent is defined as the mass of a resin containing one equivalent of epoxy groups (JIS K7236), and the smaller the value, the greater the epoxy group content. For the epoxy group-containing olefin polymers C-1 to C-13, the epoxy equivalent was calculated based on the maximum absorbance of the carbonyl peak of the FT-IR absorbance spectrum and the calibration curve. Specifically, a calibration curve was prepared in advance to correlate the maximum absorbance of the carbonyl peak of the FT-IR absorbance spectrum of the epoxy group-containing olefin polymer (C) with the content of glycidyl methacrylate determined by NMR measurement, and the content of glycidyl methacrylate was calculated from the maximum absorbance of the FT-IR absorbance spectrum of C-1 to C-13 using the calibration curve prepared, and converted into the epoxy equivalent. The calculation results of the epoxy equivalent are shown in Table 4.

[0051] [Table 4] C-3: Ethylene-glycidyl methacrylate copolymer (Bondfast BF-2C (Sumitomo Chemical Co., Ltd.)) C-4: Ethylene-glycidyl methacrylate copolymer (Bondfast BF-30C (Sumitomo Chemical Co., Ltd.)) C-5: Ethylene-glycidyl methacrylate copolymer (Bondfast BF-E (Sumitomo Chemical Co., Ltd.))

[0052] <Production of polyolefin composition> Example 1 A vessel was charged with hydrated cellulose fibers consisting of 20 parts of cellulose fibers (a1) and 44 parts of water, and the water was distilled off under reduced pressure at 80° C. 6 parts of a vinyl polymer (a2-1) having a carboxyl group and 40 parts of diethylene glycol diethyl ether were added and stirred at 140° C. Thereafter, the water and diethylene glycol diethyl ether were distilled off under reduced pressure to obtain a cellulose fiber mixture (A1). 26 parts of the cellulose fiber mixture (A1) and 24 parts of polypropylene (Prime Polypro (registered trademark) J108M, manufactured by Prime Polymer Co., Ltd.) as the polyolefin (B) were charged and melted in a vessel heated to 170°C and stirred at 50 revolutions per minute. The mixture was stirred for 2 minutes at 50 revolutions per minute, and then stirred for 10 minutes at 100 revolutions per minute. Further, 44 parts of the polypropylene and 6 parts of the epoxy group-containing olefin polymer (C-1) were charged and melted. The mixture was stirred at 50 revolutions per minute for 2 minutes, and then stirred at 100 revolutions per minute for 5 minutes to obtain a polyolefin composition. A press film was made using the obtained polyolefin composition, and the number of coarse particles of 1 mm or more was visually counted to confirm whether the composition was mixed uniformly, and it was confirmed that the number was less than 5.

[0053] (Examples 2 to 28) A polyolefin composition was obtained in the same manner as in Example 1, except that the type and amount of the vinyl polymer (a2) having a carboxyl group, the amount of the polyolefin (B), and the type and amount of the olefin polymer (C) containing an epoxy group were changed as shown in Table 5.

[0054] Comparative Example 1 20 parts of cellulose fiber (a1) and 30 parts of polypropylene (Prime Polypro (registered trademark) J108M, manufactured by Prime Polymer Co., Ltd.) as polyolefin (B) were charged and melted in a vessel heated to 170°C and stirred at 50 revolutions per minute. The mixture was stirred at 50 revolutions per minute for 2 minutes, and then stirred at 100 revolutions per minute for 10 minutes. Further, 50 parts of the polypropylene was charged and melted, and the mixture was stirred at 50 revolutions per minute for 2 minutes, and then stirred at 100 revolutions per minute for 5 minutes to obtain a polyolefin composition.

[0055] Comparative Example 2 20 parts of cellulose fiber (a1) and 30 parts of polypropylene (Prime Polypro (registered trademark) J108M, manufactured by Prime Polymer Co., Ltd.) as polyolefin (B) were charged and melted in a vessel heated to 170°C and stirred at 50 revolutions per minute. The mixture was stirred at 50 revolutions per minute for 2 minutes, and then stirred at 100 revolutions per minute for 10 minutes. Further, 49 parts of the polypropylene and 1 part of the epoxy group-containing olefin polymer (C-7) were charged and melted, and the mixture was stirred at 50 revolutions per minute for 2 minutes, and then at 100 revolutions per minute for 5 minutes to obtain a polyolefin composition.

[0056] Comparative Example 3 A vessel was charged with hydrated cellulose fibers consisting of 20 parts of cellulose fibers (a1) and 44 parts of water, and the water was distilled off under reduced pressure at 80° C. 2 parts of a vinyl polymer (a2-1) having a carboxyl group and 40 parts of diethylene glycol diethyl ether were added and stirred at 140° C. Thereafter, the water and diethylene glycol diethyl ether were distilled off under reduced pressure to obtain a cellulose fiber mixture (A1). 22 parts of the cellulose fiber mixture (A1) and 28 parts of polypropylene (Prime Polypro (registered trademark) J108M, manufactured by Prime Polymer Co., Ltd.) as the polyolefin (B) were charged and melted in a vessel heated to 170°C and stirred at 50 revolutions per minute. The mixture was stirred at 50 revolutions per minute for 2 minutes, and then stirred at 100 revolutions per minute for 10 minutes. Further, 50 parts of the polypropylene was charged and melted, and the mixture was stirred at 50 revolutions per minute for 2 minutes, and then stirred at 100 revolutions per minute for 5 minutes to obtain a polyolefin composition.

[0057] (Comparative Examples 4 to 7) Except for changing the type and amount of the vinyl polymer (a2) having a carboxyl group and the amount of the polyolefin (B) as shown in Table 5, polyolefin compositions were obtained in accordance with the method described in Comparative Example 3.

[0058] <Production of Molded Article Containing Polyolefin Composition by Injection Molding> The obtained polyolefin composition was placed in an injection molding machine (manufactured by Imoto Machinery Co., Ltd.) with the cylinder temperature set at 200° C., to obtain a dumbbell-shaped test piece.

[0059] <Evaluation of polyolefin composition> (Measurement of bending properties) The flexural modulus of the obtained dumbbell-shaped test pieces was measured using a universal testing machine ("Tensilon (registered trademark) RTM-50" manufactured by Orientec Co., Ltd.). The results are shown in Table 5.

[0060] (Impact strength measurement) The obtained dumbbell-shaped test pieces were subjected to an Izod impact test using an impact tester ("IT" manufactured by Toyo Seiki Seisakusho, Ltd.) Measurements were carried out five times for each sample, and the average values ​​are shown in Table 5.

[0061] (Method of evaluating elastic modulus and impact strength) In order to obtain a polyolefin composition with excellent mechanical strength, it is important to have both elastic modulus and impact strength. Therefore, instead of comparing the magnitude relationship between the elastic modulus and impact strength, the product of the elastic modulus and impact strength was calculated, and the mechanical strength was judged based on the magnitude. The evaluation results are shown in Table 5.

[0062] (Impact strength evaluation method) Impact strength is 14kJ / m 2 In the following cases, it was determined that the impact strength was not improved. The results of the determination are shown in Table 5. For example, in Comparative Examples 3 to 5, the elastic modulus improves as the content of (A1) increases, but the impact strength hardly changes. In such a situation, the product of the elastic modulus and the impact strength becomes large even though the impact strength is not improved. For this reason, the above-mentioned criteria were set.

[0063] [Table 5]

[0064] From the results of Example 6 and Comparative Examples 1, 2 and 3, it is seen that the polyolefin composition obtained by the production method using in combination the vinyl polymer (a2) having a carboxyl group and the olefin polymer (C) containing an epoxy group as defined in the present invention has excellent mechanical properties that cannot be achieved by not containing them or by only containing them alone.

[0065] From the results of Examples 6, 7, 12, 13, 22, and 23 and Comparative Examples 3, 4, and 5, it can be seen that even if the content of the vinyl polymer (a2) having a carboxyl group and the olefin polymer (C) containing an epoxy group as defined in the present invention is increased or decreased, a polyolefin composition having superior mechanical properties can be obtained as compared with the case where the olefin polymer (C) containing an epoxy group is not contained.

[0066] From the results of Examples 1 to 5 and Examples 9, 11 and 13, it can be seen that when the parts by mass of the epoxy group-containing olefin polymer (C) relative to the parts by mass of the cellulose fibers (a1) are equal, Examples 9, 11 and 13 in which the epoxy group-containing olefin polymer (C) is a reaction product (C1) of a (meth)acrylate having a glycidyl group and polypropylene and / or a copolymer (C2) of a (meth)acrylate having a glycidyl group and propylene and the epoxy equivalent of the epoxy group-containing olefin polymer (C) is 23,000 or less, provide polyolefin compositions having superior mechanical properties compared to Examples 1 to 5 in which (C) is a reaction product of a (meth)acrylate having a glycidyl group and polyethylene or a copolymer with ethylene.

[0067] The results of Examples 27 and 28 and Comparative Example 4 show that even when the epoxy group-containing olefin polymer (C) is a reaction product (C3) of a (meth)acrylate having a glycidyl group, a styrene, and polypropylene and / or a copolymer (C4) of a (meth)acrylate having a glycidyl group, a styrene, and propylene, a polyolefin composition having superior mechanical properties can be obtained as compared with a case not containing the epoxy group-containing olefin polymer (C).

Claims

1. A step (1) of mixing cellulose fibers (a1) with a vinyl-based polymer (a2) having a carboxyl group to obtain a cellulose fiber mixture (A1); A step (2) of mixing the cellulose fiber mixture (A1), the polyolefin (B), and the olefin polymer containing an epoxy group (C). A method for producing a polyolefin composition comprising the steps of:

2. 2. The method for producing a polyolefin composition according to claim 1, wherein the vinyl polymer (a2) having a carboxyl group contains at least one selected from the group consisting of a styrene / (meth)acrylic resin and a (meth)acrylic resin.

3. The method for producing a polyolefin composition according to claim 1, characterized in that the epoxy group-containing olefin polymer (C) is a reaction product (C1) of a (meth)acrylate having a glycidyl group with polypropylene and / or a copolymer (C2) of a (meth)acrylate having a glycidyl group with propylene, and satisfies the following (i) and (ii): (i) The cellulose fiber (a1) contains 5 parts by mass or more and 1,000 parts by mass or less of an olefin polymer (C) containing an epoxy group relative to 100 parts by mass of the cellulose fiber (a1). (ii) The epoxy equivalent of the epoxy group-containing olefin polymer (C) is 142 or more and 23,000 or less.

4. 2. The method for producing a polyolefin composition according to claim 1, wherein the epoxy group-containing olefin polymer (C) is a reaction product (C3) of a (meth)acrylate having a glycidyl group, a styrene, and polypropylene, and / or a copolymer (C4) of a (meth)acrylate having a glycidyl group, a styrene, and propylene.

5. A method for producing a molded article, comprising using a polyolefin composition obtained by the method according to any one of claims 1 to 4.